Propagation of Dachsous-Fat Planar Cell Polarity - Ambegaonkar, Abhijit A. (2012)
The Fat pathway controls both planar cell polarity (PCP) and organ growth [1, 2]. Fat signaling is regulated by the graded expression of the Fat ligand Dachsous (Ds), and the cadherin-domain kinase Four-jointed (Fj). The vectors of these gradients influence PCP [1], whereas their slope can influence growth [3, 4]. The Fj and Ds gradients direct the polarized membrane localization of the myosin Dachs, which is a crucial downstream component of Fat signaling [5–7]. Here we show that re-polarization of Dachs by differential expression of Fj or Ds can propagate through the wing disc, which indicates that Fj and Ds gradients can be measured over long range. Through characterization of tagged genomic constructs, we show that Ds and Fat are themselves partially polarized along the endogenous Fj and Ds gradients, providing a mechanism for propagation of PCP within the Fat pathway. We also identify a biochemical mechanism that might contribute to this polarization by showing that Ds is subject to endoproteolytic cleavage, and that the relative levels of Ds isoforms are modulated by Fat.